Metalloproteinases in hoof laminar tissue of equine submitted to intraluminal small colon obstruction - Canello, V. A. [UNESP] (2018)
The aim of this study was to evaluate the blood leukocytes and the MMP-2 and -9 expression in the hoof laminar tissue of horses undergoing intraluminal small colon obstruction. Laparotomy and the small colon obstruction was performed in eight healthy horses, inserting a ball in the intestinal lumen. The ball was inflated to 80 mmHg pressure and the occlusion was maintained for 4 hours. The blood was collectedBlood samples were taken before the obstruction (M0), immediately after intestinal clearance (M4), and every 12 hours until completeuntil 72 hours (M12, M24, M36, M48, M60 and M72). The hoof biopsies were performed at M0, M4, and M72 and the samples were subjected to zymography analysis. There was an increase in leukocytes in M12 and M24, due to the increase in segmented neutrophils and band neutrophils, which decreased as of M36. According to zymography technique not observed changes were not not observed in MMP-2 and -9, possibly due to the low intensity of the small colon lesions. Wherefore, it is concludedIn conclusion, that the inflammatory changes resulting from small colon obstruction were not enough to cause changes in the expression of MMP-2 and -9 in the hoof laminar tissue.